(untitled) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2020)
The present study aims to characterize the scientific production about endangered species of the Xenarthra, a group that occurs in the Brazilian Cerrado. This descriptive and quantitative research was conducted using the Scopus database. The study species were selected using the International Union for Conservation of Nature (IUCN) red list of endangered species. Four species of endangered xenarthrans occurring in the Cerrado were identified. A total of 205 publications until 2017 were cataloged, including 99 (48%) publications on Myrmecophaga tridactyla (giant anteater), 73 (36%) publications on Bradypus variegatus (brown-throated sloth), 27 (13%) publications on Priodontes maximus (giant armadillo) and six publications (3%) on Tolypeutes tricinctus (brazilian three-banded armadillo). The areas of knowledge in general biology with the highest number of publications were ecology (22%), zoology (22%) and morphology (20%). Only 9% of the publications included genetic studies, moreover there is no genetic study on the Brazilian three-banded armadillo and on the giant armadillo in Brazil. Brazil had the highest number of published articles (112) (54%), the University of São Paulo (USP) (20 publications), the State University of São Paulo (UNESP) (9 publications), the Federal University of Goiás (UFG) (11 publications) and University of Brasilia (UnB) (8 publications) stood out, with 46 scientific publications combined. Therefore, it was possible to determine an urgent need for further studies about these species, especially in genetic, since population genetic diversity is one of the international criteria for placing a species on the endangered species list. Keywords: Brown-throated sloth. Giant anteater. Brazilian three-banded armadillo. Giant armadillo.